The legacies of slavery in and out of Africa - Graziella Bertocchi (IZA Journal of Migration, 2016)
The slave trades out of Africa represent one of the most significant forced migration experiences in history. In this paper, I illustrate their long-term consequences on contemporaneous socio-economic outcomes, drawing from my own previous work on the topic and from an extensive review of the available literature. I first consider the influence of the slave trade on the 'sending' countries in Africa, with attention to their economic, institutional, demographic, and social implications. Next, I evaluate the consequences of the slave trade on the 'receiving' countries in the Americas. Here, I distinguish between the case of Latin America and that of the USA. Overall, I show that the slave trades exert a lasting impact along several contemporaneous socio-economic dimensions and across diverse areas of the world.
Keywords: J47; J15; O15; N30; P48; Z10; 330; Sklaverei; Handel; Wirkungsanalyse; Entwicklung; Soziale Lage; Wirtschaftsgeschichte; Afrika; Lateinamerika; USA; Amerika